Marketing Mix Factors on Consumer’s Perspectives and Brand Equity Affecting Brand Loyalty of Thai Franchise Coffee Consumers in Bangkok - Chanwitkan, Natticha; Intuluck, Watit (Dusit Thani College Journal, 2020)
The purposes of this research were (1) to study the demographic factors and service behavior of Thai consumers affecting brand loyalty of Thai franchise coffee shops in Bangkok and (2) to study marketing mix factors from the consumer's perspectives and brand equity factors that affect brand loyalty among Thai franchise coffee consumers in Bangkok. This is a quantitative research using a questionnaire to collect the total data of 400 Thai consumers who used the services at Thai franchise coffee shops in Bangkok. The procedure used when selected coffee shops is “Simple random sampling”, randomly pick out 4 coffee shops which located in Thailand. For coffee shops’customer, 100 customers for each brand will be chosen based on “Quota sampling”method. The statistics used for data analysis were frequency distribution, percentage, mean and standard deviation (SD). The hypothesis-testing included the t-test analysis of differences, the analysis of variance with F-test, The analysis of the differences in the mean pair by Least Significant Difference method and the multiple regression analysis. The results of the research showed that most of the respondents were female in generation Y who were mainly single with a bachelor's degree. They were mostly a private employee with an average monthly income of 30,001 - 40,000 baht. The frequencies in using the franchise coffee shops were 2-3 times per week between the hours 06:00 - 09:00 hrs. The average cost per single-use of franchise coffee shops was 51-70 baht. The reason for the use of franchise coffee shops was the product’s taste. Overall, marketing mix on consumer’s perspectives and brand equity affecting brand loyalty at a high level. In the hypothesis testing in which t-test was used to analyze the differences and F-test was applied to analyze the fluctuations, it shows that differences in level of education and average salary affected brand loyalty of coffee franchise customers in Bangkok. Moreover, the differences in frequency of consumption, amount spent and reasons of consumption affected customer’s loyalty towards brands. by using the multiple regression analysis with the enter method, the results showed that in general, the factors that affected the brand loyalty of Thai franchise coffee consumers in Bangkok. Both marketing mix on consumer’s perspectives and brand equity together had a positive relationship with the brand loyalty of Thai franchise coffee consumers in Bangkok. The factors used in this study were positively correlated with brand loyalty and can predict brand loyalty of Thai franchise coffee consumers in Bangkok at 45.6% (R² = .456). From this research, entrepreneurs should pay attention to the service marketing mix in every attribute. With good experience from service, that could bring a positive attitude towards the brand resulting in brand loyalty and repeated purchase.